Polycyclic Polyprenylated Acylphloroglucinols: An Emerging Class of Non‐Peptide‐Based MRSA‐ and VRE‐Active Antibiotics. Issue 50 (17th November 2017) - Guttroff, Claudia; Baykal, Aslihan; Wang, Huanhuan; Popella, Peter; Kraus, Frank; Biber, Nicole; Krauss, Sophia; Götz, Friedrich; Plietker, Bernd
Abstract: In the past 20 years, peptide‐based antibiotics, such as vancomycin, teicoplanin, and daptomycin, have often been considered as second‐line antibiotics. However, in recent years, an increasing number of reports on vancomycin resistance in pathogens appeared, which forces researchers to find novel lead structures for potent new antibiotics. Herein, we report the total synthesis of a defined endo‐type B PPAP library and their antibiotic activity against multiresistant S. aureus and various vancomycin‐resistant Enterococci . Four new compounds that combine high activities and low cytotoxicity were identified, indicating that the PPAP core might become a new non‐peptide‐based lead structure in antibiotic research. Abstract : A defined endo ‐type B PPAP library was synthesized, and antibiotic activity against methicillin‐resistant S. aureus (MRSA) and various vancomycin‐resistant Enterococci (VRE) was evaluated. Four new compounds with high activity and low cytotoxicity were identified, indicating that the PPAP core might become a new non‐peptide‐based lead structure in antibiotic research. PPAP=polycyclic polyprenylated acylphloroglycinol.